Identité Ethnique et Comportement Politique: le comportement électoral d’un Groupe de Tsiganes Musulmans de Thrace de l’Ouest en Grèce - Marantzidis, Nikos; Mavromatis, Georges (Études helléniques / Hellenic Studies, 2000)
Ethnic community and Political behaviour: The electoral behaviour of a group of Muslim gypsies in West Thrace in Greece. This study attempts to relate the notion of ethnic group with that of political-electoral behavior. The empirical field of analysis will be based on a group of Muslim gypsies in Thrace. The theoretical starting point of the present article is the correlation between the characteristics of the ethnic group which are determined by historical circumstances and do not stand for physical or almost physical realities. These characteristics originate from the level of significance of the occurring differences between the ethnic group and other groups as acknowledged by the former, whereas this significance derives from the resulet of various influences. The residents of Ifestos in the city of Komotini, are Muslims and speak Turkish. These are the elements that define the Muslim minority in Greece. However their electoral behaviour differs from the rest of Komotini’s Muslim minority. Concluding this essay will try to trace the reasons for this attitude and proceeds further to interpretations that could become generalized.